Facilitating charge transfer through an atomic coherent interface of a novel direct Z-scheme BiVO4@Cu3SnS4 heterojunction to boost photocatalytic performance. Issue 32 (1st August 2022) - Liu, Fangting; Chen, Chengcheng; Zhang, Qiaoyu; Zhang, Zhengguo; Fang, Xiaoming
Abstract : Cu3 SnS4 was deposited on the surface of each BiVO4 crystal to acquire a core–shell direct Z-scheme heterojunction with an atomic coherent interface, which interface facilitated the charge transfer and thus led to much enhanced photocatalytic performance. Abstract : Direct Z-scheme photocatalytic systems are very promising composite photocatalysts, and their photocatalytic performance is highly associated with the quality of the interface within them. Herein, a novel direct Z-scheme heterojunction with a coherent interface has been presented for the first time. Specifically, the heterojunction was constructed by dispersing pre-prepared BiVO4 crystals into the reaction system to synthesize Cu3 SnS4, followed by a hydrothermal reaction. It is shown that Cu3 SnS4 was deposited on the surface of each pre-prepared BiVO4 crystal as a thin layer via heterogeneous nucleation to acquire a core–shell heterojunction. The BiVO4 @Cu3 SnS4 heterojunction was found to possess an atomic coherent interface, which is formed through the bonding between the (121) plane of BiVO4 and the (112) plane of Cu3 SnS4, originating from the matching in the crystalline lattice between the two planes. The coherent interface facilitated the charge transfer from Cu3 SnS4 to BiVO4 owing to the difference in their Fermi levels, thereby forming a built-in electric field pointing from Cu3 SnS4 to BiVO4 . Reduced fluorescence emission and a shortened carrier lifetime reveal an obvious reduction in the inter-band charge recombination for the optimal BVO@CTS-0.19 sample. Consequently, BVO@CTS-0.19 shows remarkably enhanced photocatalytic performance in MO degradation, Cr 6+ reduction and oxygen evolution. The Z-scheme charge transfer mechanism for BVO@CTS-0.19 was verified by a suite of techniques. This work provides a universal strategy for building a coherent interface to develop high-performance direct Z-scheme heterojunctions.